The Fourth Element Targeting Hypothesis of Alzheimer's Disease Pathogenesis and Pathophysiology - Kuljiš, Rodrigo O. (Frontiers in Neurology, 2010)
Despite well over a century of research on all forms of the disorder known as Alzheimer’s disease (AD), it is still not known whether the condition targets initially neurons, glial cells, other cellular elements in the brain, or components of cells, such as synapses, or molecules independently of their cellular compartmentalization, or otherwise (e.g. specific neuronal circuits). Multiple lines of highly suggestive but as yet insufficient experimental evidence are discussed here to formulate the hypothesis that AD results from primary (i.e. direct and initial) or secondary targeting of what we designate as the Fourth Element Cell (4EC): a relatively recently identified type of brain cell that exhibits features in common with neurons (e.g. synapses, participation in glutamatergic and GABAergic neurotransmission), astrocytes, oligodendrocytes and their precursors, but is in other respects clearly distinct from all of them. The 4EC is proposed to be the main target of both: (1) converging insults (i.e. not true “causes”) that over time cause sporadic forms of AD as postulated by the Danger Signal Hypothesis — which was not formulated with 4EC in mind — as well as (2) the causes of inherited (i.e. familial) forms of neurodegeneration that resemble certain aspects of the clinical manifestations of sporadic AD.